2022
DOI: 10.1101/2022.02.24.481814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LUBAC is required for RIG-I sensing of RNA viruses

Abstract: The ability of cells to mount an interferon response to virus infections depends on intracellular nucleic acid sensing pattern recognition receptors (PRRs). RIG-I is an intracellular PRR that binds short double stranded viral RNAs to trigger MAVS-dependent signalling. The RIG-I/MAVS signalling complex requires the coordinated activity of multiple kinases and E3 ubiquitin ligases to activate the transcription factors that drive type I and type III interferon production from infected cells. The linear ubiquitin … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 45 publications
(50 reference statements)
3
4
0
Order By: Relevance
“…Together, these data indicate that HOIP E3 ligase activity plays a minor role in promoting RLR signaling and IFN induction, that may be obscured during viral infection, suggesting possible viral antagonism of RLR signaling or linear ubiquitination, or additional role(s) for HOIP in viral infection beyond innate RNA-sensing. These results corroborate findings from a recent study that reported a partial requirement for HOIP protein and HOIP E3 ligase activity for RIG-I signaling in A549 cells, reportedly through an interaction with and regulation of NEMO and TBK1 (37).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Together, these data indicate that HOIP E3 ligase activity plays a minor role in promoting RLR signaling and IFN induction, that may be obscured during viral infection, suggesting possible viral antagonism of RLR signaling or linear ubiquitination, or additional role(s) for HOIP in viral infection beyond innate RNA-sensing. These results corroborate findings from a recent study that reported a partial requirement for HOIP protein and HOIP E3 ligase activity for RIG-I signaling in A549 cells, reportedly through an interaction with and regulation of NEMO and TBK1 (37).…”
Section: Resultssupporting
confidence: 92%
“…These findings suggest that the LUBAC regulates a component(s) common to MDA5 and RIG-I signaling, likely at the level of MAVS, or downstream of MAVS, where the signaling by both RLRs converges. This is in line with findings by Liu et al (36) and Teague et al (37), which support a model in which linear ubiquitin chains generated by HOIP facilitate the recruitment and retainment of NEMO to the MAVS signaling complex, which in turn recruits and activates kinases that activate IRF3 and NF-kB. Liu et al also reported possible redundancy between the LUBAC and TRAF2 in promoting MAVS signaling, which may partly explain why the LUBAC is not absolutely required for RLR-mediated IFN induction.…”
Section: Hoil1 Promotes Ubiquitination Of Lgp2supporting
confidence: 93%
See 3 more Smart Citations